2016
DOI: 10.1371/journal.pone.0165585
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Gastroenteritis Virus Infection Enhances SGLT1 and GLUT2 Expression to Increase Glucose Uptake

Abstract: Transmissible gastroenteritis virus (TGEV) is a coronavirus that causes villus atrophy, followed by crypt hyperplasia, reduces the activities of intestinal digestive enzymes, and disrupts the absorption of intestinal nutrients. In vivo, TGEV primarily targets and infects intestinal epithelial cells, which play an important role in glucose absorption via the apical and basolateral transporters Na+-dependent glucose transporter 1 (SGLT1) and facilitative glucose transporter 2 (GLUT2), respectively. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…TGEV infection has been shown to increase the level of SGLT protein expression at 48 h, which was consistent with previous reports by Dai Y. Yang, et al Virus Research 280 (2020) 197901 et al (Dai et al, 2016). Moreover, in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…TGEV infection has been shown to increase the level of SGLT protein expression at 48 h, which was consistent with previous reports by Dai Y. Yang, et al Virus Research 280 (2020) 197901 et al (Dai et al, 2016). Moreover, in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Human cytomegalovirus (HCMV), a herpesvirus, induces the sugar transporter, GLUT4 to increase glucose uptake during infection [ 53 ]. Whereas, transmissible gastroenteritis virus (TGEV), a coronavirus, induces multiple sugar transporters EGFR, SGLT1, and GLUT2 for glucose uptake [ 54 ]. Rhinoviruses (RVs) are responsible for the majority of upper airway infections, and they enhance the expression of the PI3K-regulated glucose transporter GLUT1; glucose deprivation from medium and via glycolysis inhibition by 2-deoxyglucose impairs viral replication [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that SGLT1 plays a critical role during the process of TGEV infection in cells. Dai et al (2016) reported that SGLT1 protein levels were upregulated and glucose uptake in the small intestine was enhanced in the early stage of TGEV infection of IPEC-J2 cells. However, later, the glucose intake of the intestinal epithelium decreased ( Dai et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated whether TGEV infection regulated the activity, abundance, and mobility of NHE3 through EGFR in IPEC-J2 cells. The spike protein (S) of TGEV combines with EGFR to activate the downstream PI3K signaling pathway, allowing TGEV to invade small intestinal epithelial cells ( Dai et al, 2016 ). Our results showed that the levels of p-EGFR and p-ERK were significantly upregulated in porcine intestinal epithelial cells after TGEV infection.…”
Section: Discussionmentioning
confidence: 99%